Management of Obstetrical Urological Emergencies - Suliman, Osman; Mohammed, Nawal; Almahdi, Faris; Altom, Sara; Hassan, Ibrahim; Alsaedi, Emad; Elmagid, Riham Abd; Elmagid, Rana Abd (Medical Science: Recent Advances and Applications Vol. 3, 2025)
Urological emergencies during pregnancy, though rare, can pose significant risks to both maternal and fetal health. Because of changes in the body during pregnancy, conditions like urinary tract infections (UTIs), pyelonephritis, nephrolithiasis, hydronephrosis, and obstructive uropathy need to be carefully managed. This systematic review aims to evaluate the management strategies, diagnostic challenges, and clinical outcomes associated with urological emergencies in pregnant women. This study is an article review of existing peer-reviewed literature on the management of urological emergencies in pregnant women. The time of study is from October 2024 to March 2025. The extracted data were analysed using tools such as the Cochrane Risk of Bias Tool. A meta-analysis was performed. Various diagnostic techniques, including ultrasound and MRI, as well as treatment options, with a focus on ensuring maternal and fetal safety, were analysed. The findings highlight the importance of a multidisciplinary approach and suggest recommendations for improving clinical practices in managing these emergencies. Minimally invasive interventions, including ureteral stents and percutaneous nephrostomy, may offer safer alternatives to traditional surgical approaches. The review concludes with a call for standardised guidelines and further research into the long-term outcomes for both mother and fetus. Advancements in imaging technology, such as high-resolution ultrasound and MRI, can enhance early detection while minimising risks to fetal development. The role of artificial intelligence and predictive analytics in diagnosing urological conditions during pregnancy should be explored to improve accuracy and efficiency. IN addition to the early intervention, especially fetal minor invasive procedures would enhance its clinical relevance and impact.